Faktor-faktor yang Berhubungan dengan Kejadian BBLR (Berat Badan Lahir Rendah) di Asia dan Afrika - Fitratur Rahmah Agustina; Diah Mulyawati Utari (Pro Health Jurnal Ilmiah Kesehatan, 2020)
According to WHO, 20 million babies born every year experience LBW, and 96.5% of them occur in developing countries. This study aims to analyze the factors associated with LBW events. The design of this study is literature review. The articles collected are grouped according to the following inclusion criteria: 1) is a cross sectional study; 2) respondents are children aged 0-59 months; 3) research locations in Asia or Africa. The results of the study show that the sex of the child has a significant relationship with LBW in India, Indonesia, Afghanistan, Armenia, Cambodia, Jordan and Tanzania. Mothers aged â‰¥ 35 years are more at risk of giving birth to LBW babies in Armenia, Cambodia, Jordan, Nepal, Pakistan, Tanzania, Zimbabwe, Burkina Faso, Ghana and Senegal. Mother's education has a significant relationship with LBW in Oman, Afghanistan, Armenia, India, Nepal, Oman, Pakistan, Jordan, Burkina Faso, Malawi, Senegal, Uganda, Tanzania, and Zimbabwe. Occupational mothers have a significant relationship with LBW only in Nepal, and Pakistan. Maternal nutritional status (IMT) has a significant relationship with LBW events in India, Cambodia, Nepal, Pakistan, Jordan, Burkina Faso, Ghana, Malawi, Senegal, Tanzania, Uganda, and Zimbabwe. Pregnancy complications have a relationship with LBW only in Indonesia, and Oman. The number of parities has a significant relationship with LBW in Indonesia, Armenia, Cambodia, Nepal, Pakistan, Burkina Faso, Ghana, Malawi, Nigeria, Tanzania, Uganda, and Zimbabwe. The number of ANC attendees has a significant relationship with LBW in India, Nepal, Pakistan, Jordan, Malawi, Tanzania, Uganda, and Zimbabwe. The economic status of the family was found to have relations with LBW in Afghanistan, Armenia, Indonesia, Cambodia, Nepal, Oman, Pakistan, Jordan, Tanzania and Zimbabwe.